PENGEMBANGAN MAHÂRAH KALÂM DENGAN STRATEGI BERMAIN PERAN (ROLE PLAY) BAGI SANTRI MA’HAD NURUL HUDA MAN TLOGO BLITAR - Rusyadi, Refki (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
Second language (Arabic) learning, focused on optimizing speaking skill with appropriate oral communication style is challenging. This phenomenon inextricably has initiated myriad of innovative methods and strategies to improve speaking skill effectively and efficiently in the schools across Indonesia. Besides, those methods and strategies can be a means of maintaining interactive atmosphere in the classroom. One of the adequate strategies is role play. In the form of play or drama instructional activities, the teachers can help students enhance their speaking skill by naturally interacting in the classroom so as to produce well appropriate expression. For broader aspect, role play as one of cooperative language learning can foster the students’ character building in its own dimension.